2003
DOI: 10.1128/jcm.41.12.5760-5763.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enzyme-Linked Immunosorbent Assays and a PCR Test for Detection of Shiga Toxins for Shiga Toxin-Producing Escherichia coli in Cattle Herds

Abstract: Antigen capture enzyme-linked immunosorbent assays (ELISAs) for the detection of Stx1 and/or Stx2 in cattle feces were validated in comparison to the Vero cell cytotoxicity neutralization test (as a "gold standard") applied in the course of a monitoring program for Shiga toxin-producing Escherichia coli in German cattle herds as a prescreening test and compared to MK1/MK2 PCR as an alternative prescreening test.Several enzyme-linked immunosorbent assays (ELISAs) have been developed for the detection of Shiga t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The nucleotide sequences of the A and B subunits of the stx 2 gene of the selected bovine O26:H11 isolate WH-01/27/017-1 (GenBank accession no. EU700491) were identical to the stx 2 (53). The Stx2 cytotoxicity for Vero cells was also very high in the O26:H11 isolates.…”
mentioning
confidence: 51%
“…The nucleotide sequences of the A and B subunits of the stx 2 gene of the selected bovine O26:H11 isolate WH-01/27/017-1 (GenBank accession no. EU700491) were identical to the stx 2 (53). The Stx2 cytotoxicity for Vero cells was also very high in the O26:H11 isolates.…”
mentioning
confidence: 51%
“…Comparative studies have shown that cytotoxicity tests are more sensitive for detection of Stx than immunological assays (48). The detection limits of any test system can be critical if the samples contain low amounts of Stx or if the assay fails to detect certain subtypes of Stx1 or Stx2 (51,53,54). Cytotoxicity tests can be used for direct Stx testing from fecal samples where immunological methods can fail (53).…”
Section: Cytoxicity Assays For Stxmentioning
confidence: 99%
“…Fermentation of sorbitol was detected on sorbitol McConkey agar (SIFIN GmbH, Berlin, Germany) and the production of EHEC hemolysin was detected on enterohemolysin agar (Haipha GmbH, Eppelheim, Germany). The expression of Shiga toxins was monitored by an enzymelinked immunosorbent assay (ELISA) using monoclonal antibodies specific for Stx1 or by the Vero cell neutralization assay described previously (54).…”
Section: Methodsmentioning
confidence: 99%